The Effects of Sediment Classification Pattern on a Water Column Organism, Ceriodaphnia dubia - Lira, Vivian Silva [UNESP]; Watanabe, Cláudia Hitomi [UNESP]; Carvalho, Marcela Merides [UNESP]; Rosa, André Henrique [UNESP]; Fracácio, Renata [UNESP] (Springer Nature, 2018)
The sediment compartment stands out because it functions as both a temporary sink of pollutants and a potential source of these elements that may become available to the water column.This study aimed to correlate the concentrations of total metals in the crude sediment and in the interstitial water with the ecotoxicity in the water column using an a modified sediment ecotoxicity test with Ceriodaphnia dubia. The results indicate that the sediment may contribute to the toxicity in the water column and that such toxicity is possibly not related to the metals present. Based on the chemical analysis of the metals, the Canadian Sediment Quality Guidelines (SQGs) would frame the sediment as non-toxic to benthic organisms, but the SQGs have no reference standards for possible effects on nektonic organisms. Due to the complexity of this compartment, it is fundamental to evaluate the interactions of the different pollutants in the system and possible effects on the nektonic organisms.
Keywords: Bioavailability; Metals; Sediment; Toxicity and reservoir